Parenting Styles, Identity Development, and Adjustment in Career Transitions: The Mediating Role of Psychological Needs. (February 2018) - Cordeiro, Pedro Miguel Gomes; Paixão, Maria Paula; Lens, Willy; Lacante, Marlies; Luyckx, Koen
Drawing from self-determination theory, this study examines how does perceived parenting and psychological needs relate to identity development and psychosocial adjustment in Portuguese 12th-grade students ( N = 462) who prepare the transition to higher education or to the job market. Path model results revealed two distinct pathways: a "growth-oriented pathway" from need-supporting parenting to integrated career exploration, commitment-making and well-being via need satisfaction and a "vulnerability" pathway from need-thwarting parenting to both diminished well-being and ill-being through need frustration. Findings suggest that perceived parental support is a protective factor, and parental thwarting a risk factor for career decision-making, but this relation is mediated by the adolescents' subjective feelings of psychological need satisfaction and frustration. Altogether, they suggest the need to customize interventions with adolescents to address "bright" and "dark" trajectories of identity development and establish a supportive counseling climate that facilitates the exploration of different aspects of self-environment in career transition periods.